PUBLIC SPEECH: LISTENING TO WOMEN IN THE VIDEOGAME INDUSTRY - de Castell, Suzanne; Skardzius, Karen (AoIR Selected Papers of Internet Research, 2018)
Since the 1990s, conversations about the dearth of women working in the video game industry have centered on three topics: 1) ways to draw more women into the field, 2) the experiences of women working in the industry, and 3) the experiences of those who once worked in the industry but left (Cassell & Jenkins, 1998; Hepler, 2017; Kafai, Heeter, Denner & Sun, 2008). While there has been considerable research on the conditions and occupational identities of video game developers, less scholarly attention has been devoted to women in games work, the barriers/obstacles and challenges/opportunities they face, or how they talk about their experiences. Our study looked to see who among the group of women who work in the games industry has already invested her time and energy to tell a public story, whether that is in a blog posting, a book chapter, a televised talk, a radio interview, or other public media, thereby building the foundations of the study by focusing on that sub-group. This paper offers a feminist methodological approach that demonstrates how discourse focused on affect can be re-read as intimately related to silences about power, and how the rhetorical constraints that public speech imposes upon what can be said about “women in games” aids us in understanding what might remain unspoken, and why.